2015
DOI: 10.3906/sag-1403-55
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer disease, inflammation, and novel inflammatory marker: resistin

Abstract: Background/aim: Inflammation may play an important role in Alzheimer disease (AD) pathogenesis. A growing amount of evidence indicates that resistin has hallmark regulatory functions such as inflammatory states. The aim of this study was to determine whether plasma resistin levels would be useful in the diagnosis of patients with AD and to investigate the relationships between resistin and other inflammatory markers such as hs-CRP and TNF-α. Materials and methods:In this cross-sectional study, 38 AD patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 33 publications
3
30
0
Order By: Relevance
“…In spite of advances in therapeutic discoveries, there is no cure for AD. Significant bodies of evidence have been documented detailing the pathogenesis of AD in relation to inflammation [3], oxidative stress [4], and beta-amyloid plaque formations [5]. In this report, we have assessed the effect UP326, a composition containing a proprietary blend of two standardized extracts from Scutellaria baicalensis and Acacia catechu for short term memory in aged rats and for speed and accuracy of processing complex information in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of advances in therapeutic discoveries, there is no cure for AD. Significant bodies of evidence have been documented detailing the pathogenesis of AD in relation to inflammation [3], oxidative stress [4], and beta-amyloid plaque formations [5]. In this report, we have assessed the effect UP326, a composition containing a proprietary blend of two standardized extracts from Scutellaria baicalensis and Acacia catechu for short term memory in aged rats and for speed and accuracy of processing complex information in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of AD is due to a combination of factors including systemic inflammation [3], oxidative stress [4], and beta-amyloid plaque formation [5]. Aging and oxidative stress are associated with declines in hippocampal processing of information [68] as demonstrated by the deficits seen in spatial learning, memory formation, and the decline in long term potentiation that is necessary for memory consolidation.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages are the main source of resistin and obesity causes a significant macrophage infiltration of visceral white adipose tissue [30, 42]. Resistin has also been reported to be expressed in chronic disease states, such as rheumatoid arthritis, atherosclerosis, obesity, diabetes, and inflammatory bowel disease [40, 48]. Several studies reported higher levels of serum resistin in psoriatic patients compared to controls [26, 36, 49].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest a direct functional effect elicited by CRP and may be explanatory for, at least in part, the pathogenesis of Alzheimer's disease . However, data to support this are scarce, and a direct inference based on comparative CRP levels should not be made with respect to the pathogenesis of Alzheimer's disease …”
Section: Crp and Ageing‐related Diseasementioning
confidence: 93%